Hubungan Tingkat Pengetahuan Tentang Program Sosialisasi Pemberantasan Jentik Nyamuk dan Sikap Tentang Sosialisasi dengan Tindakan Masyarakat untuk Memberantas Nyamuk Aedes aegypti dan Penyakit DBD - Rachma Fitriani, Areta; Manalu, S. Rouli; Suryanto Gono, Joyo Nur (Interaksi Online, 2024)
Dengue hemorrhagic fever (DHF) cases, caused by mosquito-borne dengue virus infections, particularly Aedes aegypti, remain endemic in many countries, especially in tropical countries like Indonesia. The number of DHF cases fluctuates from year to year. Even though DHF cases have decreased this year, there is no guarantee that they will continue to decline in the following years. Semarang is no exception, as it is one of the areas experiencing a dengue outbreak. The Semarang City Government, along with various sectors, has made efforts to reduce the spread of Aedes aegypti and dengue through public awareness and education programs, as well as mosquito larvae eradication activities. Despite the implementation of programs to control the mosquitoes that cause DHF, there has been no significant progress in reducing the number of DHF cases. This research aims to clarify the relationship between knowledge, attitudes, and behaviors in efforts to eradicate mosquito larvae, particularly in the Semarang area. An explanatory research type and survey method were used in this study. The study population consists of residents in Meteseh Village who have received and participated in the socialization activities on mosquito larvae eradication (MLE). This research employed a non-probability sampling technique, and the sampling method used was accidental sampling. The data collection process was conducted by distributing questionnaires. The research results showed that the relationship between the level of knowledge about the socialization program on mosquito larvae eradication (X₁) and attitudes toward socialization (X₂) with community based Aedes aegypti mosquito eradication activities and dengue fever (Y) indicates a relationship. This was demonstrated by the results of Kendall’s tau (????) analysis, based on calculations using SPSS version 26, which produced a significance value of 0.00 and < 0.05, thus confirming the existence of a significant relationship.